Editorial: The "New Monetary Policy" - A Critical Appraisal - Giuseppe Fontana; Claude Gnos; Achim Truger (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2006)
First paragraph: The »New Monetary Policy« (NMP) is the major stabilisation policy associated with the so-called »New Consensus« (NC) view in macroeconomics. NC is the dominant view in modern mainstream economics. Its major tenets are (1) the supply-side determined equilibrium level of unemployment (e.g. NAIRU), and, related to it, (2) the acceptance of the long-run Phillips curve. Within this classical framework, the NC has first explored and then supported a role for short-run effective stabilisation policies, which have usually meant aggregate demand fine-tuning via changes in the short-run nominal interest rate controlled by the central bank. The contributions to this special issue, which contains some of the papers presented at the workshop on Macroeconomics and Macroeconomic Policy organized by the Research Network Alternative Macroeconomic Policies (Germany), the Post Keynesian Economic Study Group (UK), and the Association pour le Développement des Études Keynésiennes (France) on 28th and 29th October 2005 in Berlin, discuss this NC view and its NMP implications from a variety of perspectives and economic traditions.
Keywords: 330